Pengaruh Budaya Organisasi, Komitmen Organisasi, dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior Pada Karyawan Tetap Perusahaan Tepung Terigu Gresik - Ningsih, Rahmawati; Aslamiyah, Suaibatul; Alkusani, Alkusani (Jurnal Mahasiswa Manajemen, 2024)
Background – Behavioral phenomenon organizational citizenship behavior of Gresik wheat flour company employees on the indicators of altruism, conscientiousness, civic virtue, and courtesy is indicated to be still quite low, while behavior on sportmanship indicators can be applied properly. Objective – This research aims to determine the influence of organizational culture, organizational commitment, and job satisfaction on organizational citizenship behavior in permanent employees of the Gresik wheat flour company. Design / Methodology / Approach – This research uses a quantitative approach with a sample of 57 respondents using total sampling technique. Data collection techniques by distributing questionnaires and data analysis techniques using descriptive statistics and multiple linear regression analysis. Findings – The results showed that organizational culture, organizational commitment and job satisfaction partially had a positive and significant effect on organizational citizenship behavior in permanent employees of the Gresik wheat flour company. Research Implication – This research can be used as a reference for the Gresik wheat flour company to encourage employee organizational citizenship behavior by strengthening the existing organizational culture within the company and paying attention to factors that can increase employee commitment and satisfaction. Limitations – This research has limitations only in a relatively small sample size, so it is considered less representative.